Experimental modal analysis of the loudspeaker system - SKRODZKA, E.B.; SĘK, A.P. (Archives of Acoustics, 1997)
This paper is concerned with an experimental modal analysis of a loudspeaker system. Based on Frequency Response Functions (FRFs) measured in about 500 points uniformly spaced on the front panel of the loudspeaker system several vibrations modes, mainly of the loudspeaker membranes, have been found. Then, the vibrations of the loudspeaker membranes were compared with vibrations of the cabinet of the loudspeaker system. It has been shown that the vibrations of the loudspeaker system cabinet were very small relative to the vibration of the loudspeaker membranes. Thus, the loudspeaker system enclosure, which may be considered as a set of vibrating plates is a source of rather week sound and may be neglected.